A time‐course study of actively stained mouse brains: Diffusion tensor imaging parameters and connectomic stability over 1 year. (23rd September 2021) - Xiao, Jaclyn; Hornburg, Kathryn J.; Cofer, Gary; Cook, James J.; Pratson, Forrest; Qi, Yi; Johnson, G. Allan
Abstract : While the application of diffusion tensor imaging (DTI), tractography, and connectomics to fixed tissue is a common practice today, there have been limited studies examining the effects of fixation on brain microstructure over extended periods. This mouse model time‐course study reports the changes of regional brain volumes and diffusion scalar parameters, such as fractional anisotropy, across 12 representative brain regions as measures of brain structural stability. The scalar DTI parameters and regional volumes were highly variable over the first 2 weeks after fixation. The same parameters were consistent over a 2–8‐week window after fixation, which means confounds from tissue stability over that scanning window were minimal. Quantitative connectomes were analyzed over the same time with extension out to 1 year. While there was some change in the scalar metrics at 1 year after fixation, these changes were sufficiently small, particularly in white matter, to support reproducible connectomes over a period ranging from 2‐weeks to 1‐year post‐fixation. These findings delineate a scanning period, during which brain volumes, diffusion scalar metrics, and connectomes are remarkably consistent. Abstract : This test/retest diffusion‐weighted (DW) MRI connectomics study determines the time period post‐fixation that an actively perfused mouse brain (C57BL/6 J) can be remeasured and still maintain consistency in result. We determined from a mix of analysis of connectomics and DW metrics that within the three distinct time periods, early (prior to 2 weeks), middle (2 to 8 weeks), and late (post 8 weeks), the early time period is the most unstable of the three time periods.